Exploring urban dynamics of crowding with COVID-19 incidence: A case study of Mumbai and Bengaluru city in India - Sudha Panda; Santanu Saha Ray (Journal of Urban Management, 2021)
Cities are the economic hubs of any country and their production efficiency increases with size and density. However, the rapid spread of COVID-19 in almost all the major cities has raised several questions on the efficacy of urban densification. The objective of this paper is to understand this dynamic interplay between crowding and virus incidence. The research seeks to explain the impact of crowding parameters (population, net and gross density, street crowding, indoor crowding) on the spread of the contagion, together with the confounding explanatory variables (government policies, socioeconomic and environmental characteristics). The study is based on two metropolitan cities of India, namely Mumbai and Bengaluru, which are the hotspots of the infection. At a time when there is a huge debate of compact cities versus sprawling cities, the results are favorable towards densification as the study reveals that other crowding variables have a much higher correlation with the infection transmission than density. In fact, density follows a sub-linear relationship with transmission rate and after a threshold density; the transmission rate is almost independent of the population density. The findings show that contrary to popular belief, dense cities are resilient to pandemics.
Keywords: 710; Density; Street crowding; Indoor crowding; COVID-19 incidence rate; Population